The clinic-level perspective on mHealth implementation: a South African case study. Issue 3 (3rd July 2018) - Wolff-Piggott, Brendon; Coleman, Jesse; Rivett, Ulrike
ABSTRACT: This exploratory investigation presents a case study of the deployment of an mHealth service in established public clinics, and assesses the findings using Activity Theory. We contribute to the limited empirical research on mHealth implementation in established public facilities, and build on work on the use of Activity Theory to frame investigations of ICT4D interventions. The study investigates the perspective of clinic staff responsible for registering women for a free maternal health messaging service. Open-ended interviews and observation sessions were used to reveal staff experiences of the implementation, and their work practices. Activity Theory analysis was adopted to help interpret the data, and identify likely dynamics leading to these specific practices. Some themes that emerged were the hierarchical nature of the medical profession and implications for task shifting, the influence of technical design choices on use patterns and issues arising from the developing-country context.